Pengaruh Kinerja Keuangan, Ukuran Perusahaan Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Perusahaan Food And Beverage Yang Terdaftar Di Bei Periode 2016-2018 - Salsalbila Junita Sari; Nur Hidayati; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe purpose of this research was to find out how the Financial Performance, Firm Size And Investment Decision has an effect on the Firm Value. Type of this Research is explanatory research. The population in this research is Company of Food and Beverages listed on the Indonesia Stock Exchange (IDX) period of 2016-2018. The sample in this study is 9 companies which uses purposive sampling technique. The method of research is multiple linear regression analysis because this research have more than one variabel. Based on The result That Financial Performance, Firm Size And Investment Decision has an effect on the Firm Value. Financial performance has not a significant affect on Firm Value, Firm Size has a significant and negative affect on Firm Value, and Investment decision has not a significant affect on Firm Value.Keyword: Financial Performance, Firm Size, Investment And Firm Value